PEMANFAATAN REJEK HIDROPULPER UNTUK MENINGKATKAN NILAI KERTAS BEKAS SEBAGAI BAHAN BAKU INDUSTRI KERTAS - Taufan Hidayat; Yusup Setiawan (JURNAL SELULOSA, 2015)
Limited case study of biorefinery implementation in paper industry has been done through the investigation of fibers component separation from hydropulper reject for papermaking. Pulper rejects was cleaned from metal contaminant, crushing, screening sequentially through the screen 6, 2, and 1 size, and drying. Reject fibers (R) then mixed with Old Corrugated Container or OCC (O) in the ratio of R:O as 100:0; 75:25; 50:50; 25:75; and 0:100. The handsheets then made at the basis weight of 70, 125, and 150 g/m2 or GSM, followed by testing and evaluating. The results showed that the furnish of reject and OCC mixing is feasible for papermaking, and still have some opportunities to develope further mechanically, chemically, and or fiber reinforcement. Based on the evaluation of handsheets quality, it is recommended that improved 70 GSM paper suitable for wrapping paper, while improved 125 and 150 GSM papers supposed to be a lainer board and fluting medium.Keywords: biorefinery, hydrapulper reject, wrapping paper, lainer board, fluting mediumABSTRAKStudi kasus terbatas tentang penerapan biorefinery di industri kertas telah dilakukan melalui penelitian pemisahan komponen serat dari rejek hidropulper untuk dimanfaatkan kembali menjadi kertas. Rejek hidropulper dibersihkan dari pengotor logam, dicacah, disaring secara berurutan melalui saringan berukuran 6, 2, dan 1 mm, dan dikeringkan. Serat rejek (R) dicampur dengan Old Corrugated Container atau OCC (O) dan komposisi R:O adalah 100:0; 75:25; 50:50; 25:75; 0:100, kemudian selanjutnya dibuat lembaran kertas dengan gramatur 70, 125, dan 150 g/m2 atau GSM. Kertas dikondisikan dalam ruang standar sebelum diuji mutu lembarannya. Hasil penelitian menunjukkan bahwa furnish campuran serat rejek dan OCC layak untuk dibuat lembaran kertas, tetapi masih memerlukan perlakuan lanjutan untuk meningkatkan mutunya. Berdasarkan peluang peningkatan mutu tersebut disarankan kertas gramatur 70 GSM digunakan untuk kertas bungkus, sedangkan kertas gramatur 125 dan 150 GSM untuk kertas lainer dan medium.Kata Kunci : biorefinery, rejek hidropulper, OCC, kertas bungkus, kertas lainer, kertas medium